2017
DOI: 10.1088/2043-6254/aa7234
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of D-xylose to furfural using acid-functionalized MWCNTs catalysts

Abstract: Acid-functionalized multi-wall carbon nanotubes (MWCNTs) catalysts were prepared by a wet chemical sonication with various acid solutions, i.e. H2SO4, H3PO4, HNO3, and HCl. Sulfonic groups and carboxyl groups were detected on MWCNTs with H2SO4 treatment (s-MWCNTs), while only carboxyl groups were presented from other acid treatments. The catalytic dehydration of D-xylose into furfural was evaluated using a batch reactor at 170 °C for 3 h under N2 pressure of 15 bar. The highest furfural selectivity was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The mixture was then bubbled with nitrogen gas (N 2 ) for 5 min to remove dissolved gases that could interfere with the dehydration reaction. Afterward, the reaction mixture was heated to 180 • C, with an average time to reach the working temperature of 65 min, and maintained at that temperature for 2 h. Reaction conditions were defined based on previous studies of Termividchakorn et al [27] and Lin et al [33].…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture was then bubbled with nitrogen gas (N 2 ) for 5 min to remove dissolved gases that could interfere with the dehydration reaction. Afterward, the reaction mixture was heated to 180 • C, with an average time to reach the working temperature of 65 min, and maintained at that temperature for 2 h. Reaction conditions were defined based on previous studies of Termividchakorn et al [27] and Lin et al [33].…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…In this scenario, the use of heterogeneous acid catalysts for the selective dehydration of xylose into FF has gained more and more attention due to their high catalytic activity, low corrosivity, good thermostability, and ease of recycling and separation of the reaction medium [23,24]. Different heterogeneous catalysts applied to FF production have been reported in the literature, including zeolites, sulfonic ion exchange resins, mesoporous silicas modified with sulfonic acid, metallic oxides, and mesoporous niobium phosphate [15,23,25,26], and, more recently, carbonaceous materials derived from LCB [26][27][28][29][30][31], such as sulfonated activated carbons [32][33][34][35][36], which have high surface area and porosity, low production cost, and ease of performing surface chemical modifications. However, the primary limitation in the utilization of these acidic solids lies in their susceptibility to deactivation in aqueous and/or biphasic systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, unwanted products called humins are generated during the conversion of polysaccharides and carbohydrates and sugars dehydration and hydration of 5-hydroxymethylfurfural (5-HMF) and furfural. Humins are a big problem in the one-pot production of bioproducts on sugar platforms as they decrease reaction yields and deactivate catalysts by poisoning [74][75][76]. Relevant studies in the literature are shown in Table 3.…”
Section: Processes For the Production Of Gvlmentioning
confidence: 99%
“…In a similar way, Termvidchakorn et al functionalised multi-wall carbon nanotubes (MWCNTs) with H2SO4, H3PO4, HCl and HNO3 (Termvidchakorn et al 2017). They employed the functionalised catalysts to form FUR from xylose and achieved the highest xylose conversion (95%) when adding Co (Co(NO3)2•6H2O was used as precursor) in 3 h at 170 °C.…”
Section: Figure 5 Illustration Of Hydrothermal Stability Of Heterogementioning
confidence: 99%